Leverage as a Moderator of the Effect of Company Size, Managerial Ownership, and Conflict of Interest on Accounting Conservatism - Sari, Siti Nurmala; Agustina, Linda (Accounting Analysis Journal, 2021)
This study aims to examine the influence of company size, managerial ownership, and conflict of interest to accounting conservatism with leverage as the moderating variable. The population was mining companies and infrastructure, utilities, and transportation companies which were listed on the Indonesia Stock Exchange (IDX) from 2015 to 2018, which are 118 companies. The sample was determined by purposive sampling which resulted in 12 companies with 36 units of analysis. The data were collected by using documentaries. The analysis techniques used descriptive and inferential with the help of IBM SPSS version 21. The results showed that managerial ownership had a negative influence and conflicts of interest had a positive influence to accounting conservatism, company size had not influenced to accounting conservatism, and leverage moderated the relationship of managerial ownership to accounting conservatism, but it was unable to moderate the relationship of company size and conflict of interest to accounting conservatism. The conclusion of this study is the low managerial ownership presses the existence of expropriation; therefore, it can increase the accounting conservatism. The high conflict of interest increases the application of accounting conservatism to reduce conflicts that occur. Meanwhile, leverage influences the company’s financial risk, therefore it is able to moderate the influence of managerial ownership to accounting conservatism. Keywords: Accounting Conservatism; Company Size; Conflict of Interest; Leverage; Managerial Ownership